2014
DOI: 10.3844/ajabssp.2014.44.54
|View full text |Cite
|
Sign up to set email alerts
|

The IMPACT OF THE POLYMER COATING NUTRISPHERE™ IN INCREASING NITROGEN USE EFFICIENCY AND CORN YIELD

Abstract: Currently, it is estimated that 50 to 60% of the N applied fertilizer is actually utilized by the crop with the remaining N lost through leaching or denitrification. A three year study was conducted at eight locations in North Carolina to examine the impact of Nutrisphere™ on corn yield, optimum N rate, maximum yield, tissue N concentration, plant biomass and N uptake. At six locations the study consisted of a split plot design where main plots were either 30% Urea Ammonium Nitrate (UAN) or 30% UAN plus Nutris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The literature on Nutrisphere‐N is mixed as to its value as a fertilizer additive. Some studies have reported crop yield increases (Gordon, 2014; Heiniger et al, 2014; Maharjan et al, 2017; Wiatrak, 2014; Wiatrak and Gordon, 2014), while others have shown little effect on crop production or N transformations (Cahill et al, 2010; Chien et al, 2014; Connell et al, 2011; Edmeades and McBride, 2012; Forrestal et al, 2016; Franzen et al, 2011; Harty et al, 2017; Henning et al, 2013; Norton, 2011). Peng et al (2015) measured a reduction in nitrate leaching from soil columns when UAN was treated with Nutrisphere‐N.…”
Section: Nitrification Inhibitors and Granular Ureamentioning
confidence: 99%
“…The literature on Nutrisphere‐N is mixed as to its value as a fertilizer additive. Some studies have reported crop yield increases (Gordon, 2014; Heiniger et al, 2014; Maharjan et al, 2017; Wiatrak, 2014; Wiatrak and Gordon, 2014), while others have shown little effect on crop production or N transformations (Cahill et al, 2010; Chien et al, 2014; Connell et al, 2011; Edmeades and McBride, 2012; Forrestal et al, 2016; Franzen et al, 2011; Harty et al, 2017; Henning et al, 2013; Norton, 2011). Peng et al (2015) measured a reduction in nitrate leaching from soil columns when UAN was treated with Nutrisphere‐N.…”
Section: Nitrification Inhibitors and Granular Ureamentioning
confidence: 99%
“…For example, under irrigated conditions, Nutrisphere-N® treated urea and/or UAN consistently reduced total NH 3 volatilization losses (Barbieri et al, 2018), increased yield in grain (Gordon, 2014;Wiatrak, 2014b) and rice (Dunn & Wiatrak, 2014) and improved yield and N uptake in corn (Maharjan et al, 2017;Wiatrak & Gordon, 2014). This is in contrast to more variable results using Nutrisphere-N® under rainfed conditions where Nutrisphere-N® increased yield of corn (Smith et al, 2014) and potatoes (Hopkins et al, 2008); Nutrisphere-N® did not reduce emissions in temperate grassland (Forrestal et al, 2016), forage bermudagrass (Connell et al, 2011), spring wheat, durum wheat (Franzen et al, 2011) and corn (Liu et al, 2019). Nutrisphere-N® did also not increase yield in temperate grassland (Harty et al, 2017), bermudagrass (Moyer & Kelley, 2008;Connell et al, 2011), Spring wheat and durum wheat (Franzen et al, 2011), corn (Liu et al, 2019;Tubbs et al, 2009), sugar beet (Norton, 2011) and perennial ryegrass (Lemus et al, 2013).…”
Section: 4mentioning
confidence: 84%
“…| Inhibitor efficacy at Rainfed sites Smith et al (2014) suggest greater yield advantages will be found when Nutrisphere™ is used under conditions where yield is not limited by lack of rainfall. For example, under irrigated conditions, Nutrisphere-N® treated urea and/or UAN consistently reduced total NH 3 volatilization losses (Barbieri et al, 2018), increased yield in grain (Gordon, 2014;Wiatrak, 2014b) and rice (Dunn & Wiatrak, 2014) and improved yield and N uptake in corn (Maharjan et al, 2017;Wiatrak & Gordon, 2014).…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that the world population will increase up to 33% by 2050, from the current 7.2 billion to 9.6 billion people [1]. To provide adequate food, fiber, and renewable energy resources to meet this growth in population, we will need to dramatically increase crop yields [2], requiring, among several strategies, increasing the use of plant nutrients such as phosphorus (P) applied in the form of fertilizers.…”
Section: Introductionmentioning
confidence: 99%